Antimalarial NADPH-consuming redox-cyclers as superior glucose-6-phosphate dehydrogenase deficiency copycats - Bielitza, Max; Belorgey, Didier; Ehrhardt, Katharina; Johann, Laure; Lanfranchi, Don Antoine; Gallo, Valentina; Schwarzer, Evelin; Mohring, Franziska; Jortzik, Esther; Williams, David L.; Becker, Katja; Arese, Paolo; et al. (Antioxidants & redox signaling, 2015)
Aims: Early phagocytosis of glucose-6-phosphate dehydrogenase (G6PD)-deficient erythrocytes parasitized by Plasmodium falciparum were shown to protect G6PD-deficient populations from severe malaria. Here, we investigated the mechanism of a novel antimalarial series, namely 3-[substituted-benzyl]-menadiones, to understand whether these NADPH-consuming redox-cyclers, which induce oxidative stress, mimic the natural protection of G6PD deficiency. Results: We demonstrated that the key benzoylmenadione metabolite of the lead compound acts as an efficient redox-cycler in NADPH-dependent methaemoglobin reduction, leading to the continuous formation of reactive oxygen species, ferrylhaemoglobin, and subsequent haemichrome precipitation. Structure-activity relationships evidenced that both drug metabolites and haemoglobin catabolites contribute to potentiate drug effects and inhibit parasite development. Disruption of redox homeostasis by the lead benzylmenadione was specifically induced in Plasmodium falciparum parasitized erythrocytes and not in non-infected cells, and was visualized via changes in the glutathione redox potential of living parasite cytosols. Furthermore, the redox-cycler shows additive and synergistic effects in combination with compounds affecting the NADPH flux in vivo. Innovation: The lead benzylmenadione 1c is the first example of a novel redox-active agent that mimics the behavior of a falciparum parasite developing inside a G6PD-deficient red blood cell (RBC) giving rise to malaria protection, and it exerts specific additive effects that are inhibitory to parasite development, without harm for non-infected G6PD-sufficient or -deficient RBCs. Conclusion: This strategy offers an innovative perspective for the development of future antimalarial drugs for G6PD-sufficient and -deficient populations. Antioxid. Redox Signal. 22, 1337-1352.
Gesehen am 25.05.2020